Scalable Fabrication of Light-Responsive Superhydrophobic Composite Phase Change Materials via Bionic-Engineered Wood for Solar–Thermal Energy Management - Yang Meng; Jiangyu Zhang; Yuchan Li; Hui Jiang; Delong Xie (Molecules)
The growing demand for sustainable energy storage solutions has underscored the importance of phase change materials (PCMs) for thermal energy management. However, traditional PCMs are always inherently constrained by issues such as leakage, poor thermal conductivity, and lack of solar energy conversion capacity. Herein, a multifunctional composite phase change material (CPCM) is developed using a balsa-derived morphology genetic scaffold, engineered via bionic catechol surface chemistry. The scaffold undergoes selective delignification, followed by a simple, room-temperature polydopamine (PDA) modification to deposit Ag nanoparticles (Ag NPs) and graft octadecyl chains, resulting in a superhydrophobic hierarchical structure. This superhydrophobicity plays a critical role in preventing PCM leakage and enhancing environmental adaptability, ensuring long-term stability under diverse conditions. Encapsulating stearic acid (SA) as the PCM, the CPCM exhibits exceptional stability, achieving a high latent heat of 175.5 J g−1 and an energy storage efficiency of 87.7%. In addition, the thermal conductivity of the CPCM is significantly enhanced along the longitudinal direction, a 2.1-fold increase compared to pure SA, due to the integration of Ag NPs and the unidirectional wood architecture. This synergy also drives efficient photothermal conversion via π-π stacking interactions of PDA and the surface plasmon effects of Ag NPs, enabling rapid solar-to-thermal energy conversion. Moreover, the CPCM demonstrates remarkable water resistance, self-cleaning ability, and long-term thermal reliability, retaining its functionality through 100 heating–cooling cycles. This multifunctional balsa-based CPCM represents a breakthrough in integrating phase-change behavior with advanced environmental adaptability, offering promising applications in solar–thermal energy systems.